Psychosis in "Cognitively Asymptomatic" Elderly Subjects is Associated With Neuritic Plaque Load, Not Neurofibrillary Tangles - Kim, Julia; Schweizer, Tom A; Fischer, Corinne E; Munoz, David G (Alzheimer disease and associated disorders, 2018)
Despite having severe Alzheimer disease pathology, some individuals remain cognitively asymptomatic (cASYM). To explore noncognitive manifestations in these cASYM individuals, we aim to investigate the prevalence and pathologic substrates of psychosis. Data were obtained from the National Alzheimer's Coordinating Center. The Neuropsychiatric Inventory Questionnaire, quick version was used to evaluate presence of psychosis. Subjects with Mini-Mental Status Examination score of ≥24 with frequent neuritic plaques (NPs) were defined as NPcASYM, and those with Braak and Braak stage of neurofibrillary tangles of V/VI were defined as NTcASYM (both groups collectively designated cASYM). Logistic regression analysis was used to examine the association between NP and neurofibrillary tangle severity and psychosis accounting for potential confounders. We identified 667 subjects with Mini-Mental Status Examination score of ≥24, of which 137 were NPcASYM and 96 were NTcASYM. NPcASYM were at significantly higher risk of having psychosis compared with those with moderate or sparse/no NP (odds ratio, 2.47; 95% confidence interval, 1.54-3.96). NTcASYM were also at higher risk compared with those with Braak and Braak stage I to IV, but the association explained by the effect of Lewy body pathology and microinfarcts. The load of NP may be an important substrate of psychosis in individuals who show no gross cognitive symptoms.